Sonographic measurement of fasting gallbladder volume in healthy adults in North-West, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Quantitative assessment of gallbladder volume (GBV) is an important tool for evaluating many pathologic conditions affecting the gallbladder (GB). Therefore, there is need to establish a baseline sonographic normogram of GBV in our locality for early detection and follow-up of subjects that may develop GB diseases.Objective:To determine the mean and range of fasting GBV and to assess the relationship between GBV and age, sex, and body mass index (BMI).Methodology:The study was a cross-sectional prospective study conducted at the Aminu Kano Teaching Hospital, Kano, North-Western Nigeria. Four hundred healthy adults aged 18–60 years were recruited for the study. Subjects were scanned using Esaote MyLab 40 (Italy) ultrasound and a 3.5 MHz curvilinear transducer after 6–8 h fasting. Scanning was done in supine and right anterior oblique positions. The length, height and width of the GB were obtained and the volume (cm3) calculated using the ellipsoid formula. The height and weight of the subjects were measured and their respective BMI calculated.Results:There were 238 males (59.5%) and 162 (40.5%) females, with an age range between 18 and 60 years and mean age of 35.6 years (±12.9). The mean fasting GBV was 24.2 cm3(±8.4 cm3), with a volume range of 11.1–50.9 cm3. The mean BMI was 23.75 Kg/m2(±8.25). GBV was found to be significantly larger in males compared to females (P= 0.043); larger in older individuals (P= 0.000); and larger in those with higher BMI (P= 0.000).Conclusion:The study has established a mean fasting GBV of 24.2 cm3among healthy adults in Kano, North-Western Nigeria. This mean showed positive correlation and variation with age, sex and BMI. The values obtained in this study are comparable with values from other geo-political zones in Nigeria and other parts of the world.